2018
DOI: 10.1155/2018/1414568
|View full text |Cite
|
Sign up to set email alerts
|

Restless Legs Syndrome in Dialysis Patients: Does the Dialysis Modality Influence Its Occurrence and Severity?

Abstract: Background Restless legs syndrome (RLS) is more prevalent in chronic kidney patients than in the general population, but it is often diagnosed late and its predictors are unknown. Purpose To diagnose RLS in a group of chronic kidney patients on dialysis, determine its frequency and severity, compare the prevalence and severity of the condition among dialytic modalities, and identify possible predictive factors in this population. Methods An observational and cross-sectional study with 326 patients who had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…Apart from these general sleep quality indices, the incidence of RLS and sleep apnoea, two parameters that might be overlooked with actigraphy, were found to be different among dialysis modalities. Using the criteria from the International Restless Legs Syndrom Study Group (IRLSSG) for the diagnosis and severity of RLS, patients on automated PD presented higher RLS severity compared with the HD group [ 43 ]. And previous PSG measurements also revealed that daytime dialysis may result in more obstructive and central apnoea as compared with nocturnal PD and HD [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from these general sleep quality indices, the incidence of RLS and sleep apnoea, two parameters that might be overlooked with actigraphy, were found to be different among dialysis modalities. Using the criteria from the International Restless Legs Syndrom Study Group (IRLSSG) for the diagnosis and severity of RLS, patients on automated PD presented higher RLS severity compared with the HD group [ 43 ]. And previous PSG measurements also revealed that daytime dialysis may result in more obstructive and central apnoea as compared with nocturnal PD and HD [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result was similar to a study conducted by Santos et al and de Menezes where this significance was due to increase in serum parathormone or due to anemia (decreased hemoglobin) irrespective of iron status. [ 24 25 ] In another study, they have attributed this to the proinflammatory nature of dialysis as a physiological basis for patients on prolonged hemodialysis. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…At present, more than 272,000 ESRD patients receiving peritoneal dialysis treatment worldwide, which accounts for ~11% of dialysis patients ( 1 ). Restless legs syndrome (RLS) is a neurological sensorimotor disorder and a severe complication in patients undergoing PD, with a prevalence rate of about 24.7% ( 2 ). Patients undergoing PD with RLS will feel an urge to move the legs especially during rest which will lead to having trouble falling asleep ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…RLS not only reduces the sleep quality of patients which induces daytime fatigue, poor mental health, and emotional anxiety, but also may increase the risk of hypertension, cardiovascular disease, and cerebrovascular disease ( 4 ). RLS seriously affects the quality of life and prognosis of patients undergoing PD, but still lacks effective treatment ( 2 ). It's essential to understand the pathogenesis of RLS.…”
Section: Introductionmentioning
confidence: 99%